Pengembangan Modul Dengan Aplikasi Edmodo Pada Materi Menulis Makalah - Yanti Juniarti; Armi Antasari; KA. Noviansyah (Jurnal Ilmiah Edukatif, 2025)
This research is the development of teaching materials module with edmodo on the material of writing papers for students of Akamigas Palembang Polytechnic, with the aim of describing the needs of students and lecturers for learning to write papers, producing teaching materials module writing papers with Edmodo, describing the results of module validation, describing the module trial, and describing the potential impact of the module on student learning outcomes. This development research uses a modification of the Jolly and Bolytho and Dick, Carey, and Carey models. Twenty students and 1 Indonesian language lecturer at Akamigas Palembang Polytechnic are the objects of this research. Data collection techniques using questionnaires and tests, the feasibility of the teaching materials developed can be seen from the validation results by three experts on 3 components of the teaching materials. Based on the results of expert validation, the total score obtained from the assessment of the feasibility of content/material, language, and media obtained a score of 90 out of a maximum score of 105 (converted to 85.71). Based on this score, it can be concluded that the Writing Paper Module with Edmodo that was developed is declared good or feasible to use. In the paired sample t-test on the essay writing test, the difference in the average pretest and posttest scores was 41,000 with a standard deviation of 9.706 and a significance level (2-tailed) of 0.000 <α (0.05), so that the Essay Writing Module with Edmodo has a potential impact on improving students' essay writing skills. The researcher concluded that the essay writing module with Edmodo produced can be used in learning activities and has a potential impact on improving students' essay writing skills.